IDENTIFICATION OF DRUG-RELATED PROBLEMS ON BETA LACTAM ANTIBIOTICS USED FOR PEDIATRIC AT A SECONDARY-CARE HOSPITAL IN CIMAHI - Zulfan Zazuli; Tomi Hendrayana; Siti Farah Rahmawati; Shalvierra Polyta Fitriah (School of Pharmacy Institut Teknologi Bandung, 2017)
WHO estimated that >50% of medicines are used inappropriately. One that posess highest risk due to inappropriate use is beta-lactam antibiotic, espescially in pediatric patient since the organ function in pediatric patient has not fully developed as in adult yet. This cross-sectional study was performed to identify drug-related problems (DRPs) occurred during beta-lactam therapy in pediatric hospitalized in a secondary-care hospital in Cimahi. A predetermined medication-use criteria based on the current literatures was created as an assessment standard tools. Furthermore, identification of DRPs based on PCNE v6.2 classification was carried out concurrently (January-March 2015) to 351 patients. As many as 458 DRPs were found including 22 cases inappropriate drugs (category C1.1), 127 cases no indication for drug (C1.2), 42 cases inappropriate combination of drugs, or drugs and food (C1.4), 1 case of too many drugs prescibed for indication (C1.6), 137 cases drug dose too low (C3.1), 89 cases drug dose too high (C3.2), 39 cases duration of treatment too short (C4.1), and 1 case of duration of treatment too long (C4.2). The potential DRPs was estimated to be occured for approximately 1-2 DRPs per patient.Keywords: drug-related problems; beta-lactam antibiotic; pediatric; pharmaceutical care